Attenuation of Hemodynamic Pressor Response during Laryngoscopy and Intubation: A Clinical Study of Premedication with Di?erent Doses of Oral Melatonin - Archana Devtara; Ankur Gandhi; Maya Damor; Sadhana Jain; Aditya Sharma; Aradhaya Verma (Academia Anesthesiologica International, 2020)
Objectives: To assess the effect of two different doses of oral melatonin premedication on the hemodynamic parameters. Subjects and Methods: Ninety patients aged between 20 to 45 years of either sex belonging to ASA grade I and II were randomly divided into three groups. This randomized prospective study was conducted on patients undergoing elective surgeries on general anesthesia. In Group-C oral Placebo was given 120 minutes before surgery, in Group M6- Tab. Melatonin 6mg and in Group M9- Tab. Melatonin 9mg was given 120 minutes before surgery. Patients were assessed for intraoperative and post-operative hemodynamic parameters at different time intervals. Results :   The   mean heart rate in Group M6 and group M9 was significantly decreased from baseline (83.63  6.7) to (81.96  6.1) and from (82.82  .09) to  (77.4  5.25) respectively, (P<0.001) while in Group C it was increased from baseline (81.2  5.33) to (92.0  4.64). Systolic blood pressure   (SBP) was increased from baseline (123.56 3.25) to (132.76 3.77) in Group C, while in Group M6 and M9 it was significantly decreased from (121.13 3.82) to (118.13 31.3) and from (122.79  3.33) to (115.96  3.44) respectively. (P<0.001) Diastolic blood pressure (DBP) in Group C was increased from baseline (80.23 2.11) to (87.70 3.48). In Group M6 and M9, it was significantly decreased from baseline (78.03 5.15) to (73.56 3.77) and from (77.51 3.87) to (71.55 3.14) respectively. (P<0.001). Conclusion: Oral melatonin in a dose of 6mg and 9mg was more effective compared to placebo but 9mg attenuated the hemodynamic response asoociated with laryngoscopy and endotracheal intubation better as compared to 6mg melatonin.Objectives: To assess the effect of two different doses of oral melatonin premedication on the hemodynamic parameters. Subjects and Methods: Ninety patients aged between 20 to 45 years of either sex belonging to ASA grade I and II were randomly divided into three groups. This randomized prospective study was conducted on patients undergoing elective surgeries on general anesthesia. In Group-C oral Placebo was given 120 minutes before surgery, in Group M6- Tab. Melatonin 6mg and in Group M9- Tab. Melatonin 9mg was given 120 minutes before surgery. Patients were assessed for intraoperative and post-operative hemodynamic parameters at different time intervals. Results :   The   mean heart rate in Group M6 and group M9 was significantly decreased from baseline (83.63  6.7) to (81.96  6.1) and from (82.82  .09) to  (77.4  5.25) respectively, (P<0.001) while in Group C it was increased from baseline (81.2  5.33) to (92.0  4.64). Systolic blood pressure   (SBP) was increased from baseline (123.56 3.25) to (132.76 3.77) in Group C, while in Group M6 and M9 it was significantly decreased from (121.13 3.82) to (118.13 31.3) and from (122.79  3.33) to (115.96  3.44) respectively. (P<0.001) Diastolic blood pressure (DBP) in Group C was increased from baseline (80.23 2.11) to (87.70 3.48). In Group M6 and M9, it was significantly decreased from baseline (78.03 5.15) to (73.56 3.77) and from (77.51 3.87) to (71.55 3.14) respectively. (P<0.001). Conclusion: Oral melatonin in a dose of 6mg and 9mg was more effective compared to placebo but 9mg attenuated the hemodynamic response asoociated with laryngoscopy and endotracheal intubation better as compared to 6mg melatonin.